The study of a mathematical model of surface reactions - Ambrazevičius, Algirdas; Puriuškis, Gintaras (Lietuvos matematikos rinkinys, 2014)
We prove the a priori estimates of a classical solution to a coupled system of parabolic and ordinary differential equations, the latter being determined on the boundary of the domain. This system describes the model of surface reactions between carbon monoxide and nitrous oxide.